Kilka uwag o dylematach badawczych transformacji postkomunistycznej = Some remarks on research dilemmas of post-communist transformation - Chałubiński, Mirosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article tackles the problem of theoretical significance of transformation experiences in Poland. Taking into account their usefulness for explaining transformations in the post-communist area, research perspectives and orientations dealing with radical system changes are presented. The analysis is focused on the idea of theoretical eclecticism, its qualities and cognitive limitations. It is aimed at answering the question of the specificity of Polish transformation in light of sociological knowledge.
Keywords: transformacja ustrojowa; transformacja postkomunistyczna